Distribution of some geochemical elements in the surface sediment of Kerteh Mangrove Forest, Terengganu, Malaysia - Yunus, Kamaruzzaman; Chuan, Ong Meng (Penerbit UKM, 2008)
Surface sediments collected from two transects (30 sampling points) in the Kerteh mangrove forest had been analyzed for Co, Cu, Pb, Zn and Cr concentrations with the Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The average concentration of Co was 8.91 ± 1.89 μg/g dry weight, Cu was 29.0 ± 12.8 μg/g dry weight, Pb was 11.7 ± 6.85 μg/g dry weight, Zn was 22.3 ± 13.7 μg/g dry weight and Cr was 13.2 ± 9.07 μg/g dry weight. Their concentrations were significantly higher near the front mangrove and declined as the sampling points of each transect near the back mangrove area. The calculated enrichment factors (EF) obtained for A and Cr can be considered to have the terigeneous in sources while Co, Cu and Pb, which had slightly higher value, were probably influenced by anthropogenic input.